Analysis of liquefaction of volcanic soil during the 2016 Kumamoto Earthquake based on boring data - K. Ogo; H. Hazarika; T. Kokusho; D. Matsumoto; S. Ishibashi; W. O. Sumartini (Lowland Technology International, 2018)
On April 16th, 2016 Kumamoto earthquake registering 7 on Japanese scale caused liquefaction in many places around Kumamoto plain. However, considering the magnitude and the distance from the hypocenter, the liquefaction-induced damage was not so huge. Most of sand boiling was observed where liquefaction is likely to happen such as near waters and on an old river channel. In addition, black sand which seems to be volcanic soil was observed as ejecta of liquefaction in many places. This paper deals with the liquefaction characteristics of volcanic soil through physical and mechanical testing, microscopic observation by SEM and liquefaction susceptibility evaluation based on boring data. According to the physical testing, the grain size distribution was typical of liquefaction susceptible sand. Many of sand boils happened on the alluvial ground, and the thick strata of volcanic soil were found there. Based on the results of liquefaction evaluation, some locations have shown the liquefaction susceptibility in spite the fact that little occurrence of liquefaction took place at those locations.